Pelatihan kewirausahaan dan pengelolaan keuangan usaha mikro:studi kasus pada penjual es krim di Manokwari: Entrepreneurship Training and Micro Business Financial Management:Case Study on Ice Cream Seller in Manokwari - Albertus Girik Allo; Dedy Riantoro (Fakultas Peternakan Universitas Papua, 2023)
Ice cream sellers from South Sulawesi are members of an organization called PCM (Manokwari Ice Cream Sellers). Their weakness is the lack of knowledge and understanding of entrepreneurship. This causes them to experience no significant changes in their welfare and patterns of economic activity. The absence of other skills, as well as the difficulty of diversifying their businesses, will reduce the income of ice cream business actors. Entrepreneurship training and financial management activities for ice cream sellers who are members of PCM Manokwari were held four times (March 04 2022, March 18 2022, April 01 2022, April 15 2022). The location for the implementation of the activity is at the Makasar Complex, Wosi-Manokwari. This activity was attended by 16 ice cream sellers, although and each subsequent meeting fluctuated, but not less than 50% of the initial total attendance. This indicates that the entrepreneurship and financial management training provided was quite well received. Keywords: Entrepreneurship training; Financial management; Ice cream sellers